A treasury of virtues sayings, sermons and teachings of Ali al-Qadi al-Quda'i : with the one hundred proverbs attributed to al-Jahiz - 'Ali ibn Abi Talib Caliph approximately 600-661 (Library of Arabic literature, 2013)
A Treasury of Virtues is a collection of sayings, sermons, and teachings attributed to 'Ali ibn Abi Talib (d. 40H/661AD), cousin and son-in-law of the Prophet Muhammad, first Shi'a Imam and fourth Sunni Caliph. 'Ali was an acknowledged master of Arabic eloquence and a renowned sage of Islamic wisdom. Through proverbs and aphorisms, sermons and speeches, prayers and supplications, epistles and contracts, testimonials and homilies, verse and dialogues, it provides instruction on how to be a decent human being.